Perancangan Dashboard Telemetry: Studi Kasus di Tim Distribusi PT X - Jeremia Jeremia; Siana Halim (Jurnal Titra, 2022)
This research aims to design a telemetry dashboard for PT X. Telemetry is a tank monitoring tool. This tool is installed for each customer or business partner of PT X. The telemetry monitoring process produces a dataset, which has to be presented to the Board of Directors of PT. X for further performance evaluation. Before using a dashboard, the team processed and visualized the dataset manually. So naturally, it was very time-consuming and prone to human error. Therefore, we designed a dashboard based on the monthly reports using a Google Data Studio in this study. Additionally, we prepared the dataset for creating the dashboard using Python and Google Sheets to reduce the processing time. The designed dashboard can provide an overview of the tank’s conditions and telemetry utilization, compare the telemetry measurement of each customer and business partner, save distribution costs and reduce the filling frequency, and monitor the KPI of delivery distribution performance.